Synthesis inhibitors of gibberellins and mango 'Tommy Atkins' seedlings growth - Mouco, Maria Aparecida do Carmo (2010)
The mango in the Brazilian semi-arid region stands out in the national scenario due to high yields and fruit quality, as well as to the possibility of all-year production due to climatic conditions and technologies which allow the management of plant growth and flowering through irrigation, pruning and use of plant growth regulators. Paclobutrazol applied to the soil is used for the production management of mangoes in most of the orchards. However, it is necessary to identify plant growth regulators which might be applied to the leaves, so as to minimize the risk of residues in the soil and to avoid inadequate application levels over several years. The present paper aimed at evaluating the effect of plant growth regulators applied to the leaves, regarding their efficiency for flowering management of mango 'Tommy Atkins'. Prohexadione-Ca, trinexapac-ethyl and chlormequat chloride at the dosage of 1.0 g a.i. plant-1 acts on the regulation of vegetative growth; the period of efficiency of the products applied to the leaves lasted 20 days for prohexadione-Ca, 30 days for chlormequat cloride, and 45 days for trinexapac- ethyl.